Effect of Small-scale Irrigation on the Farm Households’ Income of Rural Farmers: The Case of Girawa District, East Hararghe, Oromia, Ethiopia - A, Beyan; H, Jema; K, Adem (Asian Journal of Agriculture and Rural Development, 2014)
Irrigation is one means by which agricultural production can be increased to meet the growing food demands in the world. This study evaluated the effect of small-scale irrigation on farm household income in production. The specific objective of this study is to identify the factors in-fluencing participation in small-scale irrigation and provides bases for policy makers in Girawa district, Eastern Hararghe zone, Oromia, Ethiopia. Both primary and secondary data were collect-ed for the study. Primary data were collected from 200 sample respondents drawn from both par-ticipant and non-participant households. Preliminary statistics and econometric models were em-ployed for data analysis. The logistic regression estimation of factors affecting participation re-vealed that age of household head, non-farm income, livestock size, size of cultivated land, dis-tance between plot and irrigation scheme, means of transportation and participation of household heads in social organization significantly affected the participation decision of households in irri-gation farming. Results showed that participation in irrigation has a significant, positive effect on farm households’ income. Therefore, policy makers should give due emphasis to the aforemen-tioned variables to increase participation in irrigation farming and improve the livelihood of rural households.